Qualidade de sementes de Cyclanthera pedata (L.) em função dos estádios de maturação e do período de repouso pós-colheita dos frutos - Bruna Bessell Almeida Porto (2016)
The Cyclanthera pedata (L.) is a non-conventional vegetable found in the North of Minas Gerais, where it is grown on a small scale by farmers. This species, which has medicinal properties, has in Peru, a yield of 7 t ha-1, however, the income potential is much higher. In Montes Claros / MG trials showed promising production to the region with incomes of up to 18 t ha-1. In the literature, there are few works that explore the agronomic characteristics of culture. The objective of this study was to determine the ideal time to extract seeds maxixe-do-reino due to the maturity and length of stay in the fruit to achieve a high standard of quality. The study was conducted in two stages, where the first was done planting the maxixe-do-reino to obtain the fruit. In the second stage, the female flowers were marked during the anthesis and fruits were harvested at 23, 28, 33 and 38 days after anthesis (DAA). Exemplary fruits, 23 and 28 DAA were post-harvest stand for 0, 60, 120 and 180 hours to then proceed to extraction the seeds. The seeds were extracted from the fruit and passed by drying in a laboratory environment for 4 days.The experimental design was completely randomized in a factorial (2x4) +2 understood that the seeds from the fruit of 23 and 28 DAA in the four rest periods, plus two additional treatments, they are the seeds from fruits at 33 and 38 DAA who did not have home. For each treatment, 4 reps were adopted. The fruits and seeds passed through biometric analysis and then the seeds were subjected to the following tests to evaluate the physiological and physical quality: germination, first count, hard seeds, dead seeds, germination speed index, length of radicle, length hypocotyl, determination of moisture content, thousand seed weight and dry weight of seeds. In the health analysis of seeds was analyzed the incidence of fungi in the seeds. The advancing age of the fruits resulted in an increase in seed quality maxixe-do-reino until the 33DAA. Harvesting fruit with 23 to 28 DAA results in low seed germination. The post harvest rest of the fruits harvested at 23:28 DAA, did not improve seed quality. The seeds reached physiological maturity to harvest the fruit at 33 DAA. During this period the fruits presented with intermediate external color from green to yellow, noting high seed quality. At 38 DAA seeds began to show a loss of quality.